Particulate air pollution and preeclampsia: a source-based analysis. Issue 8 (28th March 2014) - Dadvand, Payam; Ostro, Bart; Amato, Fulvio; Figueras, Francesc; Minguillón, María-Cruz; Martinez, David; Basagaña, Xavier; Querol, Xavier; Nieuwenhuijsen, Mark
Abstract : Objectives: To investigate the association between preeclampsia and maternal exposure to ambient particulate matter (PM) with aerodynamic diameter less than 10 μm (PM10 ) and 2.5 μm (PM2.5 ) mass and sources. Methods: Our analysis was based on a hospital cohort of pregnant women (N=3182) residing in Barcelona, Spain, during 2003–2005. Positive matrix factorisation source apportionment (PMF2) was used to identify sources of PM10 and PM2.5 samples obtained by an urban background monitor, resulting in detection of eight sources. We further combined traffic-related sources (brake dust, vehicle exhaust and secondary nitrate/organics) to generate an indicator of combined traffic sources. Logistic regression models were developed to estimate the association between preeclampsia and exposure to each PM source and mass separately during the entire pregnancy and trimester one, adjusted for relevant covariates. Results: For the exposure during the entire pregnancy, we found a 44% (95% CI 7% to 94%) and a 80% (95% CI 4% to 211%) increase in the risk of preeclampsia associated with one IQR increase in exposure to PM10 brake dust and combined traffic-related sources, respectively. These findings remained consistent after an alternative source apportionment method (Multilinear Engine (ME2)) was used. The results for PM2.5 mass and sources and also exposure during trimester one were inconclusive. Conclusions: Risk of preeclampsia was associated with exposure to PM10 brake dust and combined traffic-related sources.